Regenerative Synergy: Combining Platelet-rich Plasma with Transcutaneous Temperature-controlled Radiofrequency for Enhanced Treatment of Stress Urinary Incontinence in Peri- and Postmenopausal Women - Smit Bharat Solanki (Journal of Mid-Life Health)
Background: Stress urinary incontinence (SUI) is a significant health concern among peri-and postmenopausal women, often leading to diminished quality of life. Transcutaneous temperature-controlled radiofrequency (TTCRF) has emerged as a minimally invasive treatment option, but its efficacy may be limited in cases of severe tissue laxity. Platelet-rich plasma (PRP) offers a promising adjunct to enhance tissue remodeling and functional recovery when combined with TTCRF. Objective: This study evaluates the safety, efficacy, and patient-reported outcomes of combining PRP with TTCRF for treating SUI in peri- and postmenopausal women, aiming to address gaps in current therapeutic strategies. Materials and Methods: A prospective, randomized controlled trial was conducted involving 80 peri- and postmenopausal women diagnosed with SUI. Participants were randomly assigned to two groups: PRP plus TTCRF (intervention group, n = 40) and TTCRF alone (control group, n = 40). Primary outcome measures included objective improvement assessed via urodynamic studies and subjective improvement evaluated using validated questionnaires (International Consultation on Incontinence Questionnaire - Short Form [ICIQ-SF] and Urogenital Distress Inventory). Secondary outcomes encompassed quality of life (Pelvic Floor Distress Inventory [PFDI-20]) and adverse event reporting. Statistical analyses were performed using SPSS version 27.0, with significance set at P < 0.05. Results: At the 12-month follow-up, the intervention group demonstrated significantly superior outcomes compared to the control group. The mean reduction in ICIQ-SF scores was 9.8 points versus 6.6 points (P = 0.001), and urodynamic parameters improved by 32% more in the PRP plus TTCRF group (P = 0.003). Quality of life, as measured by PFDI-20, showed a 22% greater improvement in the intervention group (P = 0.002). Conclusion: Combining PRP with TTCRF represents an innovative, minimally invasive approach that enhances tissue regeneration and functional recovery in peri- and post-menopausal women with SUI. These findings highlight the potential of PRP to augment the efficacy of TTCRF and warrant further investigation in larger, multicenter trials.